AgBiS2-TPP nanocomposite for mitochondrial targeting photodynamic therapy, photothermal therapy and bio-imaging under 808 nm NIR laser irradiation. (11th September 2019) - Sun, Mingdi; Yang, Dan; Wang, Chen; Bi, Huiting; Zhou, Yuan; Wang, Xiangxi; Xu, Jiating; He, Fei; Gai, Shili; Yang, Piaoping
Abstract : AgBiS2 nanodots as an NIR light-excited photosensitizer produce a PDT effect, which is reported for the first time. Abstract : 808 nm near-infrared (NIR) light-induced biological theranostics is gradually becoming a popular method for cancer treatment. Meanwhile, mild synthetic methods to prepare medicines and gentle treatment conditions for cancer patients are becoming increasingly important to oncotherapy. Herein, tiny AgBiS2 nanodots were synthesized via a simple method, and for the first time, discovered to produce a photodynamic therapy (PDT) effect for cancer treatment under 808 nm laser irradiation, which was characterized by both chemical probe and intracellular reactive oxygen species (ROS) detection. Subsequently, because tumor cells have more mitochondria than normal cells to generate more energy to maintain rapid growth for population expansion, and triphenylphosphonium (TPP) can transport tiny nanoparticles into the mitochondria, the as-synthesized AgBiS2 nanodots were combined with TPP in a facile route. In our design, the AgBiS2 nanodots exhibit photothermal properties and TPP can enhance the photothermal properties of the AgBiS2 nanodots to a certain extent, which make the AgBiS2 -TPP nanocomposite applicable in photothermal therapy (PTT). Furthermore, the AgBiS2 -TPP nanocomposite showed a remarkable computed tomography (CT) imaging performance for tumor diagnosis. The facile synthetic strategy, satisfactory anticancer effect, CT imaging and mitochondrial targeting of the AgBiS2 -TPP nanocomposite demonstrate its high potential in the anticancer field.